From Strategy to Adaptability: How Strategic Leadership Shapes Organizational Resilience via Adaptive Culture - Dewi Siti Mahmudah; Novita Dwi Indriyani (Journal of Marketing Management and Innovative Business Review, 2025)
This study investigates the effect of strategic leadership on organizational resilience, with adaptive culture serving as a mediating variable. Using a quantitative approach and partial least squares structural equation modeling (PLS-SEM), data were collected from 160 organizational respondents. The results indicate that strategic leadership does not directly affect organizational resilience. However, strategic leadership significantly influences adaptive culture, which in turn has a positive and significant effect on resilience. Furthermore, adaptive culture is found to fully mediate the relationship between strategic leadership and organizational resilience. These findings highlight the pivotal role of adaptive culture as a transmission mechanism through which strategic leadership fosters resilience. Theoretically, the study contributes to the leadership and resilience literature by confirming the mediating role of culture. Practically, it underscores the importance of cultivating adaptive cultural values to translate leadership into tangible resilience capabilities, especially in dynamic and uncertain environments.